Everolimus in Anaplastic Thyroid Cancer: A Case Series - Harris, Ethan J.; Hanna, Glenn J.; Chau, Nicole; Rabinowits, Guilherme; Haddad, Robert; Margalit, Danielle N.; Schoenfeld, Jonathan; Tishler, Roy B.; Barletta, Justine A.; Nehs, Matthew; Janne, Pasi; Huang, Julian; et al. (Frontiers in Oncology, 2019)
Background: Anaplastic thyroid cancer (ATC) is a very aggressive disease and accounts for over 50% of thyroid-cancer related deaths. mTOR inhibition has shown anti-tumor activity in ATC. We report our experience treating patients with ATC with everolimus off-protocol. Methods: Patients with confirmed ATC and treated with everolimus at DFCI were identified and reviewed retrospectively. NexGen sequencing was performed, and radiologic responses were correlated with mutational profile. Results: Five patients were treated from 2013-2016. Three patients had a response, which included one patient who achieved a partial response for 27.9 months, and two patients who had stable disease for 3.7 and 5.9 months, respectively. Genomic analysis was available in two patients and revealed that the partial responder had mutations involving the PI3K/mTOR pathway. Conclusion: Everolimus has anti-tumor activity in ATC, and responses may correlate with mutations involving the PI3K/mTOR pathway. Further studies are warranted.